OOPERATION OF SMALL AND MEDIUM-SIZED TOURISM ENTERPRISES (SMTES) WITH TOURISM STAKEHOLDERS IN THE MAŁOPOLSKA REGION – TOP MANAGEMENT PERSPECTIVE APPROACH - KRZYSZTOF BORODAKO (Tourism & Management Studies)
The purpose of this paper is to understand the difference in number of relations of small and medium-sized tourism enterprises (SMTE) with tourism stakeholders in the region. This research used an email survey sent to tourism CEOs, directors or owners of SMTEs in the Małopolska Region, focusing on its capital city - Cracow (Poland). All three groups of respondents in SMTEs were understood in the research as the top management of these companies. The study conducted made it possible, on the basis of the statistically significant results, to analyze the differences as regards the level of cooperation between companies depending on the company size, micro firms and SMTEs, their belonging to different subsectors and the company age. Observations show that such differences exist and should be used by the SMTEs managers and tourism policy makers. The largest part of the researched sample usually cooperates with one to five partners from each stakeholder group. A surprising conclusion was the high level of cooperation with competitors from the same subsector – almost one third of the accommodation and catering firms collaborate with more than five competitors.